Development of different fabrication methods for (electro) chemical sensors on paper and their analytical applications - Gongoni, Juliana Luz Melo (2023)
There has been an increasing search for alternative, low-cost platforms for sensing target molecules. This work initially presents analytical platforms coupled with colorimetric and fluorescence using chromatographic papers as a substrate. Both detection systems were accomplished with an organic molecule, Se-BODIPY, containing a chromophore that changes color due to its specificity to palladium II, allowing its quantification. A smartphone captured images of color changes for subsequent analysis with the GIMP 2.10.24 software. Colorimetric detection provided a limit of detection (LOD) and quantification (LOQ) of 46.1 and 153.8 mol L-1, while fluorescence detection yielded 16.0 and 53.2 mol L-1, respectively. Next, electrochemical sensors were produced by pyrolyzing Kraft paper with a CO2 laser source. After fabrication, the resulting sensors were electrochemically activated, allowing nitrite determination in environmental and biological samples, with LOD and LOQ of 4.3 and 14.3 mol L-1, respectively. Laser pyrolysis also produced gold-modified electrochemical sensors. The modification decreased the peak-to-peak separation from 154 to 116mV for the [Fe(CN)6]4-/[Fe(CN)6]3- probe, demonstrating improvement in their electrochemical performance. The electrochemical sensors were applied to determine bacterial activity in probiotics and yogurts in a quick 10 minutes of analysis, showcasing comparable results to conventional glassy carbon electrodes. Paper-based electrochemical sensors were manufactured in different atmosphere conditions as a straightforward way of improving their electrochemical performance. The conditions included laser pyrolysis in argon, oxygen, and ambient conditions. Changing the pyrolysis medium formed different carbon structures besides modulating their electrochemical responses for analytical applications. Finally, the inkjet printing technique made electrochemical sensors onto poly(vinyl chloride) (PVC) substrate with commercial silver ink. This sensor detected picric acid and hydrogen peroxide with LOD and LOQ of 12 and 40 mol L-1 and 15 and 25 mol L-1, respectively. The devices were also used for glucose detection in real and artificial saliva samples, with LOD and LOQ of 15 and 30 mol L-1. Therefore, its possible to create and measure targeted analytes with simple yet robust sensors made from daily-use materials.